Moesian and Dacian sigillata – exploring regional patterns: A methodological approach using chemical analysis by WD-XRF and p-ED-XRF - Daszkiewicz, Małgorzata; Schneider, Gerwulf; Baranowski, Marcin; Petrut, David; Rusu-Bolindeţ, Viorica; Man, Nicoleta (Rei Cretariae Romanae Fautorum Acta, 2022)
Chemical analysis by wavelength-dispersive X-ray fluorescence (WD-XRF) was used to establish reference groups for Moesian sigillata produced in Butovo, Pavlikeni and Novae in present day Bulgaria. Sigillata finds from Dacian sites (Buciumi, Brâncoveneşti) were compared. Long-distance traded imports were easily identified as coming from Gaul (Lezoux, Les Martres de Veyre, La Graufesenque). The rest of the finds and ten samples of local sigillata from Dacia (Micăsasa, Cristeşti) could not be distinguished so easily by chemical analysis. Multivariate methods yielded ambiguous results and therefore in publications they should not replace the original analysis results, as it is only the latter which allow the interpretation of data to be verified, e.g. by taking possible alteration effects into account. Finally, the finds could not be attributed securely to any of the regional workshops in Moesia or Dacia. More analyses are necessary to establish secure reference groups. With all samples the use of portable XRF was tested. This method could be very important for future studies of museum objects.